Boosting Performance through Motivation and Career Growth: Evidence from the Gresik Customs and Tax Services Office - Alfarisi, Salman; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose –  This study aims to examine the effects of work motivation and career development on employee performance at the Customs and Tax Supervision and Services Office of Gresik District. Design/Methodology/Approach – This study employs an explanatory quantitative research design to analyze the relationship between independent variables, namely work motivation and career development, and the dependent variable, namely employee performance. Data were analyzed using SPSS version 25 to conduct statistical tests and measure the influence of the research variables. Findings – The results indicate that work motivation has a positive and significant effect on employee performance. Career development also has a positive and significant effect on employee performance. These findings demonstrate that improving employee motivation and providing effective career development opportunities are important strategies for enhancing employee performance in government service organizations. Originality/Value This research is original in simultaneously analyzing work motivation and career development within a public-sector context. The findings provide practical value by offering evidence-based recommendations for improving employee performance through better managerial policies and career planning systems.